IDMONEIFORM TUBULIPORINA (BRYOZOA, STENOLAEMATA): MORPHOLOGICAL FEATURES, PROBLEMS IN SYSTEMATICS, AND NEW TAXA - Viskova L.A. (My University, 2004)
Since the frontal sides of the colonies of idmoneiform Tubuliporina follow a single plan, the developmental features of various heterozooecia acquire great taxonomic significance independently of the shape and position of gonozooecia. New kinds of such heterozooecia have been discovered in thin sections: reptozooecia, stenozooecia, angulizooecia, and cryptozooecia. Those idmoneiform Tubuliporina that clearly show a different kind of zooecial dimorphism are considered to belong to the family Idmoneidae Busk, 1859. New taxa from the Upper Cretaceous-Paleogene of Belarus and Kazakhstan are described: Idemona occultata gen. et sp. nov., Castellia repentina gen. et sp. nov., Erkosonea certa sp. nov., Lagonoecia neoglobulifera sp. nov., and L. cujulusensis sp. nov.